L’événement en révolution - Chaymaa Hassabo; Matthieu Rey (Revue des Mondes Musulmans et de la Méditerranée)
By bringing together two sets of facts, namely both the mass protests which erupted in Cairo between 30 June and 3 July 2013 and fights which broke out in Damascus between 13 and 23 July 2012, this article sheds light on writing narratives of events. It is argued that events can be considered as a heuristic tool and a specific manner to construct social science. First, it is argued that this category has not received full attention in the social sciences, and then we are looking how to write narrative based on events. At a certain moment, several temporalities are brought together in a specific situation and demonstrate a complex interplay. As situations move quickly, actors emerge and disappear, perceptions are constantly changing. In the context of revolution, which is characterized by a high level of change, it is concluded that only narratives of the event that describe the event for itself, ultimately provide access to the complexity of social reality.